Tuli Sensorineural Pasca Meningitis Streptococcus Suis: Sebuah Topik Kajian Strategis Bidang Ilmu Neuroinfeksi - Sudewi, AA Raka; Pramitasuri, Tjokorda Istri; Susilawathi, Ni Made; Adi Tarini, Ni Made; Mahardika, I Gusti Ngurah Kade; Sukrama, I Dewa Made (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2022)
Sensorineural deafness as a result of Streptococcus suis (S. suis) meningitis is a serious hazard to worldwide public health and one of the strategic study concerns in neuroscience. There is currently no treatment plan for sensorineural deafness brought on by S. suis meningitis that can significantly enhance quality of life. Controlling S. suis meningitis-related sensorineural deafness is therefore vital for the area of neurology. This review of the literature seeks to provide an overview of the scientific literature on the epidemiology, etiology, and features of deafness as they pertain to sensorineural hearing loss brought on by S. suis meningitis. Spiral Ganglion Neurons, hair cells in the cochlea, and brain-derived neurotrophic factor in the peripheral auditory system interact with one another in the etiology of sensorineural deafness, according to recent studies.